Asian Youth Travellers Insights and Implications (Perspectives on Asian Tourism,, 2018)
This book offers a bird's-eye view of the current trends, opportunities, and challenges related to Asian youth travellers, and it also presents a holistic framework for future research to build upon. Managerial and policy implications are provided for the tourism and hospitality industry and government agencies to better accommodate the needs of Asian youth travellers - a unique and diverse market that is yet to be fully unveiled to the world. This book investigates the key characteristics that define contemporary Asian youth travellers, adopting a broad definition of Asia. While it includes relatively mature markets, it also features emerging markets in Southeast Asia, South Asia, and West Asia. The book looks at different forms of tourism undertaken by Asian travellers, encompassing educational tourism, adventure tourism, working holiday, self-driving tourism, dark tourism, volunteer tourism, and cultural tourism. A wide range of topics are discussed, from history to current trends, from motivations to constraints, from the influence of culture and religion on travel behaviour to the search of social freedom through travel, and from destination choice to destination avoidance. The findings and interpretations are drawn from diverse and novel research methods, such as netnography, visual anthropology, historiography, interview, focus group, survey, and document analysis.